Profile and Feasibility of Cocoa Farming System in Kolaka, Southeast Sulawesi - Ermiati Ermiati; Abdul Muis Hasibuan; Agus Wahyudi (Jurnal Tanaman Industri dan Penyegar, 2014)
Limitation of land tenure and productivity in farmers’ level causing lower farmers income. Kolaka District is one of cocoa main producers in Southeast Sulawesi with a large number of farmers. The objective of this study was to investigate the profile and feasibility of cocoa farming system in farmers level. The research was conducted at Atula and Dangia Village, Ladongi Subdistrict, Kolaka Regency, Southeast Sulawesi, in April to July 2012. Data was collected by survey method and direct interview with 30 farmers.  Data was analyzed descriptively and feasibility analysis method with criteria of benefit cost ratio (B/C ratio), net present value (NPV), and internal rate of return (IRR). The result showed that cocoa farming system is feasible (NPV of IDR19,646,384.00; B/C ratio of 2,87 and IRR of 51%). Farmers income was of IDR7,697,674.00 per year (IDR641,743.00 per month). If the yield is constant (773 kg/ha), then price break even point (BEP) is IDR8,043.00/kg. If the price is constant (IDR18,000.00/kg), then BEP of yield is 345,5 kg/ha/year. This result showed that cocoa farming gives a relatively low level of income for farmers, eventhough it is feasible. Based on those analysis, minimum area of 2 ha per households or productivity of 1.5 ton/ha/yr required to meet income decent life.